Three principles for preparing Al wire with high strength and high electrical conductivity. Issue 5 (May 2019) - Hou, J.P.; Li, R.; Wang, Q.; Yu, H.Y.; Zhang, Z.J.; Chen, Q.Y.; Ma, H.; Wu, X.M.; Li, X.W.; Zhang, Z.F.
Abstract: The trade-off relation between the strength and the electrical conductivity has been a long-standing dilemma in metallic materials. In the study, three key principles, i.e. elongated grains, sharp texture and nano-scale precipitates, were presented for preparing Al wire with high strength and high electrical conductivity based on the specially designed experiments for breaking the mutually exclusive relation between the strength and the electrical conductivity. The results show that the elongated grains could lead to a higher electrical conductivity in Al wire without sacrificing the strength; while, the <111> sharp texture can efficiently strengthen the Al wire without influencing the electrical conductivity. Furthermore, nano-scale precipitates with proper size can simultaneously improve the strength and electrical conductivity of Al alloy wire. Under the guidance of the above three key principles, Al wires with high strength and high conductivity were prepared.